1984
DOI: 10.1901/jaba.1984.17-343
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Social/Vocational Skills to Retarded Adults With a Modified Table Game: An Analysis of Generalization

Abstract: In this study, a social skills training program for institutionalized mildly or moderately retarded adults was extended to include skills relevant to vocational settings. Target behaviors involving a verbal action or reaction within six skill areas were taught using a commercially available board game, Sorny, and a specially designed card deck. The training program featured response specific feedback, self-monitoring, individualized reinforcers, and individualized performance criterion levels. Using a multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Social skills training for parents with intellectual disabilities has been taught successfully in previous studies using the group format, although the materials were limited in the complexity of adult-adult scenarios and depiction of parent-child situations (Foxx et al 1983(Foxx et al , 1984Fantuzzo et al 1986). Whilst training focused on raising social awareness and contextual relationship issues, this did not involve observable, discrete measures of change in parents' social skills.…”
Section: Discussionmentioning
confidence: 99%
“…Social skills training for parents with intellectual disabilities has been taught successfully in previous studies using the group format, although the materials were limited in the complexity of adult-adult scenarios and depiction of parent-child situations (Foxx et al 1983(Foxx et al , 1984Fantuzzo et al 1986). Whilst training focused on raising social awareness and contextual relationship issues, this did not involve observable, discrete measures of change in parents' social skills.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Foxx et al [19] adapted a commercially available board game to train social and vocational skills to developmentally delayed adults. The game contingencies increased social/vocational skills in all targeted areas.…”
Section: Has This Approach To Educational Games Been Undertaken Before?mentioning
confidence: 99%
“…* Each card contained a situation designed to elicit a verbal response before a subject's game piece could be moved and a number that indicated the number of spaces that could be moved. The situations were either adapted from those used in our previous studies (38 situations) Foxx et al, 1984a; 'Acopy of the 48 situation items and sample correct responses can be obtained by writing the senior author. Storey, & Rogers, 1984b) or designed specially for adolescents (10 situations).…”
Section: Settings and Materialsmentioning
confidence: 99%
“…and categories (i.e., acting and reacting) were initially developed for use with mentally retarded individuals, our research with psychiatric inpatients suggested that they covered a wide range of social situations that occur in any interactional group. In fact, Foxx, McMorrow, and Mennemeier (1984a) and Foxx, McMorrow, Bittle, and Ness (1986) demonstrated that the component areas and categories could be used to analyze freely occurring verbalizations in undisturbed and ongoing group interactional situations. This was accomplished by separating individual responses into one of the component areas (e.g., criticism) and categories (i.e., actor, reactor) and utilizing scoring criteria (see Table 1) that were relevant to that class of verbal behaviors.…”
mentioning
confidence: 99%